(3fgGjI GdYbhd aj GdcdGe aj OQGjI GdCUhds - (3eMeO Hf YeQ Hf GdMSf Hf GdMSjf GdJjej GdHcQj, CHh YHO Gddg, aNQ GdOjf GdQGRqj,J (B606 (3g` s ((3eMeO Hf eMeO Hf eMeO(B- (3GdHdNi s)
(3ChdgG (B:s
(3CeG HYO MeO Gddg Ydi JSGHb BdGFI hJdGMb fYeGFg aEf TQa GdYde jXgQ ef YOI ChLg CMOgG TQa GdeYdhe hdG Tc Cf GdZQV GdCge hGdeWdhH GdCYXe ef Yde GdcdGe eYQaI PGJ Gddg JYGdi hUaGJg hcjajI CaYGdg s
(3BNQgG (B:s
(3GdaUd GdSGHY YTQ ai MUQ GdUaGJ Cbhi eG bjd ajg Ef Gddg JYGdi cdafG HeYQaJg KdGFO dfG ef WQjb Edi Pdc hEdG hbY GdJcdja HGdeMGd hGdWQjb dfG Edi Pdc djS Edi CaYGd Gddg JYGdi hdjcf BNQ cdGefG ai GdUaGJ GdMeO ddg Mb MeOg hGdUdGI Ydi NjQ Ndbg es
(3GdfSNI HgG MhGTs
(3HgG fXGe GdJYbjHIs
(3cJHJ HYV GdcdeGJ hYfGhjjf GdaUhd HGdMeQI s
(3bQf GdfSN (B:s
(3GdbQf GdSGOSs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdJhMjO hGdedd hGdfMds